Philosophical and Ideological Foundations Guiding People’s Multiparty Democracy - Pahari, Bharat Raj (State, Society and Development: PMPD Perspectives, 2026)
People’s Multiparty Democracy (PMPD), formulated by Madan Bhandari as the guiding ideological principle of the Communist Party of Nepal (Unified Marxist Leninist) (CPN[UML]), emerged from the distinctive historical experiences of both the Nepali and international communist movements at a moment of profound global ideological contestation. Situated at the intersection of Marxist theory and the concrete socio-political realities of a multiethnic, multilingual, and geographically diverse society, PMPD constitutes a systematic attempt to reconceptualize the foundations of progressive social transformation. This study examines PMPD as a creative and innovative development of Marxism, interrogating its philosophical, ideological, and theoretical underpinnings through a qualitative analysis of primary theoretical texts, academic literature, and historical documentation tracing the evolution of Marxist thought. The findings reveal that PMPD introduces substantive innovations to classical Marxist theory: while orthodox Marxism locates the origins of discrimination, exploitation, and oppression exclusively in economic relations and class structures, PMPD advances the proposition that the diversity inherent in nature itself generates social plurality, rendering differences in ideas, beliefs, and consciousness additional sources of domination and inequality. To address this expanded understanding of social contradiction, Bhandari introduced the principles of democratic competition and initiative as instruments of political governance, complemented by an emphasis on democratic organizational practice and collective leadershi—The significance of PMPD resides in its theoretically grounded yet empirically validated argument that political legitimacy must be secured and renewed through periodic electoral consent—a proposition affirmed by the CPN (UML)’s electoral achievements during a period when communist movements worldwide were confronting deep organizational and ideological crises. As such, PMPD represents a distinctive and enduring contribution to contemporary Marxist thought.